THE IMPLEMENTATION OF THE ZERO BURNING POLICY CONCEPT IN THE AGREEMENT OF TRANSBOUNDARY HAZE POLLUTION IN LAWS AND REGULATIONS IN INDONESIA IS ASSOCIATED WITH A RESTORATIVE APPROACH IN EFFORTS TO RECOVER THE ECONOMY - Irfan Hanafi; Teuku Syahrul Ansari (Universitas Labuhanbatu, 2023)
This paper analyzes how the Indonesian government implements its laws and regulations related to the Zero Burning Policy concept that has been mandated by the ASEAN AGREEMENT ON TRANSBOUNDARY HAZE POLLUTION towards ASEAN member countries including Indonesia. The concept of the Zero Burning Policy mandated by the ASEAN AGREEMENT ON TRANSBOUNDARY HAZE POLLUTION requires all countries that ratify it not to clear land using the burning method where forest fires are very disruptive to the economy, both for the company's economic activities and for the community. This paper will explain more about how the laws and regulations in Indonesia accommodate the concept of Zero Burning Policy against the provisions of the legislation, whether it is in accordance with what is mandated or vice versa and what the concept of solving forest fire problems is for economic and environmental recovery.Keywords : Forest Fires, Zero Burning Policy, Economic Recovery.